Grounded Theory and Its Application to Study the Situation of Unmarried Women - Arf, Shelan (Al-Adab Journal, 2024)
The research is an attempt to study the situation of Unmarried Woman (Spinster) through the use of the Constructivist Grounded Theory method by Kathy Charmaz, one of the methodologies that used in qualitative research. The study aims to distinguish how to use the Constructivist Grounded Theory method and its analytical steps in studying Unmarried Women (Spinsters). It focuses on the challenges that Unmarried Women (Spinsters) face and the methods they resort to cope with the difficulties. Though, to achieve this goal, the researcher conducted interviews with Unmarried Women (Spinsters), in Iraq in the city of Sulaimani. Researcher used the method of semi-structured in-depth interviews, the sample is a purposive sampling, and the snowball sampling was used to reach the respondents. The steps of the Constructivist Grounded Theory method were carefully followed using the MAXQDA program in the initial coding and focused coding process, the study reached at a set of important core categories that reflect the reality of the life of Unmarried Women (Spinsters)in Iraqi society (the city of Sulaimani as an example). The study found that the unmarried woman (spinster) faces various challenges, such as the family’s control over her life, so, not allowing her to speak to others, and the father and brother’s control over their lives. Unmarried Women (Spinsters) must return to them and obtain their approval in all matters in the women lives. The study found that Unmarried Women (Spinsters) follow various strategies and methods to cope with the challenges and difficulties in their lives, such as studying, while others indicated that seeking help from God and devoting time to worship is the best way to cope with these difficulties.